(untitled) (Modern American Journal of Biological and Environmental Sciences, 2026)
Throughout the entirety of the territory, as a direct consequence of low pasture productivity, there is a pronounced shortage of fodder and a generally poor level of provision for livestock breeders. It is estimated that approximately 50% of dehkan (peasant) and private farming enterprises lack adequate access to necessary fodder resources. Whilst in the irrigated zones this deficiency is primarily a consequence of the reduction in arable land allocated for fodder crops (such as alfalfa, maize, and others), in the desert zones it is predominantly driven by the severe degradation and low biomass yield of natural pastures, excessive grazing pressure, and a fundamental mismatch between the increasing number of livestock and the available pasture areas. In connection with these persistent challenges, a consistent